How our body influences our perception of the world - Harris, Laurence R.; Carnevale, Michael J.; D’Amour, Sarah; Fraser, Lindsey E.; Harrar, Vanessa; Hoover, Adria E. N.; Mander, Charles; Pritchett, Lisa M. (Frontiers in Psychology, 2015)
Incorporating the fact that the senses are embodied is necessary for an organism to interpret sensory information. Before a unified perception of the world can be formed, sensory signals must be processed with reference to body representation. The various attributes of the body such as shape, proportion, posture, and movement can be both derived from the various sensory systems and can affect perception of the world (including the body itself). In this review we examine the relationships between sensory and motor information, body representations, and perceptions of the world and the body. We provide several examples of how the body affects perception (including but not limited to body perception). First we show that body orientation effects visual distance perception and object orientation. Also, visual-auditory crossmodal-correspondences depend on the orientation of the body: audio “high” frequencies correspond to a visual “up” defined by both gravity and body coordinates. Next, we show that perceived locations of touch is affected by the orientation of the head and eyes on the body, suggesting a visual component to coding body locations. Additionally, the reference-frame used for coding touch locations seems to depend on whether gaze is static or moved relative to the body during the tactile task. The perceived attributes of the body such as body size, affect tactile perception even at the level of detection thresholds and two-point discrimination. Next, long-range tactile masking provides clues to the posture of the body in a canonical body schema. Finally, ownership of seen body parts depends on the orientation and perspective of the body part in view. Together, all of these findings demonstrate how sensory and motor information, body representations, and perceptions (of the body and the world) are interdependent.